2021
DOI: 10.3389/fmed.2021.748915
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Risk Prediction Model Using Recursive Feature Elimination Algorithm for Acute-on-Chronic Liver Failure in Chronic Hepatitis B Patients With Severe Acute Exacerbation

Abstract: Background: Patients with chronic hepatitis B (CHB) with severe acute exacerbation (SAE) are at a progression stage of acute-on-chronic liver failure (ACLF) but uniform models for predicting ACLF occurrence are lacking. We aimed to present a risk prediction model to early identify the patients at a high risk of ACLF and predict the survival of the patient.Methods: We selected the best variable combination using a novel recursive feature elimination algorithm to develop and validate a classification regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…54 Yu et al developed another four-variable model, including age, prothrombin time, serum total bilirubin level, and alanine aminotransferase level, abbreviated as the PATA model, for risk identification of ACLF. 55 However, these models have limitations. First, they were derived from retrospective rather than prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Yu et al developed another four-variable model, including age, prothrombin time, serum total bilirubin level, and alanine aminotransferase level, abbreviated as the PATA model, for risk identification of ACLF. 55 However, these models have limitations. First, they were derived from retrospective rather than prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…ACLF = acute-on-chronic liver failure. 55 However, these models have limitations. First, they were derived from retrospective rather than prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Real-life cohorts have confirmed that the pre-ACLF phenotype is characterized by heightened systemic inflammation. 31,40 Notably, the [43][44][45] More recently, Dual-energy CT quantification of extracellular liver volume has been associated with such progression independently from liver disease severity parameters. 46 However, most of the predictive models are derived from single-center retrospective studies, and…”
Section: Clinical Implication Preventionmentioning
confidence: 99%
“…Studies investigating factors associated with APASL‐ACLF (mainly in the setting of severe acute exacerbation of chronic hepatitis B infection) occurrence have also been conducted. They have identified that age, liver disease severity (bilirubin, prothrombin time, MELD score) or HBV viral load were associated with the risk of progression toward ACLF 43–45 . More recently, Dual‐energy CT quantification of extracellular liver volume has been associated with such progression independently from liver disease severity parameters 46 .…”
Section: Clinical Implicationmentioning
confidence: 99%